The effect of chronic regulatory focus and social comparison on undergraduates’ intertemporal choices under gain-loss frame - Liu, Dan; Zhang, Yuan; Geng, Xiaowei (Frontiers in Psychology, 2023)
Intertemporal choice refers to decisions involving tradeoffs among costs and benefits occurred at different times. It remains unclear whether college students' intertemporal decision making under the gain and loss frames is affected by their chronic regulatory focus. Currently, experiment 1 investigated the influence of college students' chronic regulatory focus on intertemporal decision making under the gain and loss frames, and experiment 2 further explored the moderating effect of social comparison (i.e., upward or downward social comparison) during this process. The results showed that intertemporal choices of participants with promotive focus was no significant difference between the gain frame and loss frame, while college students with preventive focus chose later and larger rewards more in loss frame than in gain frame. Social comparison moderated the effects of the chronic regulatory focus on college students' intertemporal choice in gain and loss frames. The upward comparison enhanced the influence of regulatory focus on intertemporal choice in the gain and loss frames, while the downward comparison weakened it.